Communication network patterns among hexahelix actors in creative economy development in Bogor Regency - Muhammad Fazrah; Robby Firliandoko; Maria Fitriah (Privietlab, 2026)
The creative economy sector has mutated into a strategic pillar for boosting macro and micro economic growth at the regional level. This study aims to analyze in depth the communication network patterns among actors in the hexahelix model collaboration through the Creative Economy Committee or Komite Kabupaten Bogor Ekonomi Kreatif (Kabekraf) in Bogor Regency, with an exclusive focus on mapping the flow of message exchange in the field. Utilizing a descriptive qualitative method, the unit of analysis focuses on the communication relationship patterns established between Kabekraf management representatives and other hexahelix actors, including government, academia, business actors, and communities. Data collection techniques were realized through in-depth interviews and a comprehensive documentation study. Data analysis in this study applies the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. Research results indicate that the communication network structure positions Kabekraf as a central hub (node) that bridges cross-sectoral relational dynamics. Communication network patterns in the field materialize in three main operational forms: an adaptive vertical flow based on digital platforms, a horizontal flow among parallel elements showing a well-established level of organic independence, and a cross-functional diagonal flow capable of dismantling conventional bureaucratic barriers while stimulating strategic program innovations Keywords: communication network patterns, creative economy, hexahelix collaboration, organizational communication, stakeholder communication